Health, wealth and progeny: explaining the living arrangements of older European women - Maria Iacovou (University of Essex, Institute for Social and Economic Research (ISER), 2000)
The increase in the numbers of older people across industrialised countries, and the increasing proportion of older people who live alone, have enormous implications for social policy in these countries. This paper uses data from the European Community Household Panel (ECHP) to analyse the determinants of living alone for elderly non-married women in Europe; and to examine how these determinants vary between different groups of countries. A number of methodological issues relating to research on living arrangements are also discussed. The main findings of the paper are that higher levels of income are related to a higher probability of living alone, although the relationship is S-shaped, with the main effect found in the second quartile in higher-income countries, and the third quartile in lower-income countries. Women with a limiting health problem are less likely to live alone in countries where social spending is relatively low, while women who have had more children are less likely to live alone in countries where residential mobility is relatively high.
Keywords: 330